Digestibilidade aparente de ingredientes proteicos de origem animal para o jundiá Rhamdia voulezi - Frei, Guilherme Rodrigo (2015)
There are several native Brazilian species with potential for fish farming, among which silver catchfish stands out, continues to feed and gain weight even at low temperatures, accepts varied diets, besides being a species with ease of reproduction and larviculture. However, for the commercial production of this species to be successful, the knowledge of the different aspects related to its nutrition and feeding is fundamental, as enables specific, nutritionally complete and environmentally correct balanced diets to be formulated and supplied to fish. In this sense, most of the ingredients used in aquaculture feeds are derived from agricultural by-products, slaughtering of terrestrial animals or fishing, one of these by-products being flours. Knowing the nutrient digestibility of these raw materials is the first step when evaluating its potential for inclusion in fish feed. The digestibility of a feed is defined as the ability with which the animal digests and absorbs the nutrients and energy contained in it. The aim was to determine the apparent digestibility coefficients (CDA) of protein ingredients of animal origin for jundiá Rhamdia voulezi. A total of 288 jundies with an initial mean weight of 285 ± 44.02 g were distributed in 24 randomized, conical-cylindrical aquariums with a useful volume of 500L. A reference diet (control) was prepared and the ingredients to be tested were included in the proportion of 30% of the test ingredient and 70% of the control diet. Chromium oxide at 0.2% concentration was used as the marker. Fecal material was collected through collecting cups. It was evaluated the Crude Protein (PB), Ethereal Extract (EE), Crude Energy (EB), Mineral Matter (MM), Phosphorus (P), Magnesium (Mg), Calcium (Ca), Zinc (Faith). The CDAs were submitted to ANOVA statistical analysis (p <0.05) when significant, the Tukey mean test (p <0.05) was applied. In general, the ingredients that had the best CDAs were viscera meal and salmon meal. These results demonstrate that jundiá accepts very well the protein ingredients of animal origin and has good capacity to digest them and to take advantage of its nutrients.